The impact of relaxing the requirements for dyspeptic Symptom Onset frequency or duration in Rome IV Criteria on the Symptom Pattern and diagnosis of functional dyspepsia - Jinsheng Wang; Junhao Wu; Xiaohua Hou; Lei Zhang (BMC Gastroenterology)
Abstract Background The Rome IV criteria for functional dyspepsia (FD) has strict requirements for symptom frequency and onset duration, making it difficult for patients to meet these criteria in clinical practice. This study aimed to investigate the impact of relaxing the Rome IV criteria on the diagnosis and symptom pattern of FD. Methods A cross-sectional, multi-center study was conducted involving 2935 consecutive broadly defined FD patients without positive findings on upper gastrointestinal endoscopy or routine examinations. Questionnaires were used to collect demographic and upper gastrointestinal symptom data. Symptom pattern was compared between Rome IV criteria defined FD patients and those defined by relaxed Rome IV criteria. Results Only 22.2% of broadly defined FD patients rigorously fulfilled Rome IV criteria. No significant difference was found for proportion of patients with dyspeptic symptoms, dysmotility-like symptoms, reflux-like symptoms, as well as severity and onset frequency of dyspeptic symptoms (all P > 0.05), between patients who didn’t fulfill Rome IV criteria for FD solely due to a duration of 3–6 months and Rome IV criteria defined FD patients. Patients with broadly defined postprandial distress syndrome (PDS) who didn’t fulfill Rome IV criteria solely due to a symptom frequency of 1–2 days per week had significantly lower symptom severity (P < 0.001), but similar postprandial symptom characteristics compared to those defined by the Rome IV criteria. Conclusions A symptom duration criterion of 3 months may be sufficient for diagnosing FD. Reducing the symptom onset frequency to no less than 1 day per week in the Rome IV criteria for PDS does not affect its postprandial symptom characteristics.